Persepsi siswa terhadap pengaruh kebiasaan membaca pada keterampilan menulis - Noverita, Zalsabilla Laily (Maliki Interdisciplinary Journal, 2024)
This study aims to explore students’ perceptions of the influence of reading habits on their writing skills in secondary school. Using a qualitative approach, data were collected through in-depth interviews and participant observation. The participants of this study were 20 students from grades 10 and 11 at a secondary school in City Y. In-depth interviews were conducted to delve into the students’ understanding of how their reading habits affect their writing abilities. The interview questions were designed openly to provide space for students to express their views and personal experiences. Additionally, participant observation was carried out during reading and writing activities in the classroom to obtain contextual data and real behaviors of students in both activities. The results of the study indicate that the majority of students have a positive perception of the influence of reading habits on their writing skills. Students revealed that regular reading helps them enrich their vocabulary, improve their understanding of grammar, and expand their insights and ideas for writing. Classroom observations support these findings by showing a correlation between students’ reading intensity and the quality of their writing. The findings of this study emphasize the importance of cultivating reading habits among students to improve their writing skills. Recommendations for educators include integrating more intensive and diverse reading programs into the curriculum, as well as providing broader access to interesting and relevant reading materials for students.